2007
DOI: 10.1002/jcb.21291
|View full text |Cite
|
Sign up to set email alerts
|

Transitional CpG methylation between promoters and retroelements of tissue‐specific genes during human mesenchymal cell differentiation

Abstract: In general, methylation of the promoter regions is inversely correlated with gene expression. The transitional CpG area between the promoter-associated CpG islands and the nearby retroelements is often methylated in a tissue-specific manner. This study analyzed the relationship between gene expression and the methylation of the transitional CpGs in two human stromal cells derived from the bone marrow (BMSC) and adipose tissue (ATSC), both of which have a multilineage differentiation potential. The transitional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 45 publications
5
47
0
1
Order By: Relevance
“…However, in our study, the methylation status of promoter CpG islands was found to be preserved in critical genes, such as SOX9 and RUNX2, during chondrogenesis. This observation may indicate a retained capability of the mesenchymal progenitor cells to change their differentiation status even after chondrogenesis, since similar observations about adipogenesis of MSCs have been reported (36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 82%
“…However, in our study, the methylation status of promoter CpG islands was found to be preserved in critical genes, such as SOX9 and RUNX2, during chondrogenesis. This observation may indicate a retained capability of the mesenchymal progenitor cells to change their differentiation status even after chondrogenesis, since similar observations about adipogenesis of MSCs have been reported (36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 82%
“…Their results demonstrated an accumulative methyl-cytosin at the endogenous Trip 10 promoter, Trip 10 downregulation, and progressive MSC to neuron and osteocyte differentiation (Hsiao et al, 2010). In contrast to that study, lack of a remarkable alteration in DNA methylation of the promoter during in vitro differentiation of MSCs into osteocytes was reported by Kang et al (2007).…”
Section: Dna Methylation In Osteogenic Differentiationmentioning
confidence: 81%
“…Osteogenic differentiation of mesenchymal cells towards osteoprogenitor and osteoblastic cells is regulated by several mechanisms, including DNA methylation. Kang et al demonstrated that promoter methylation changes during mesenchymal cell differentiation [50]. Likewise, it has been proposed that active demethylation of gene promoters (i.e., osteocalcin, osterix, or Runx2), via GADD45-dependent mechanisms, is involved in the ostegenic differentiation of mesenchymal cells [51].…”
Section: Role Of Dna Methylation In Establishing a Bone Cell Phenotypementioning
confidence: 99%